2018
DOI: 10.1177/2050157918761491
|View full text |Cite
|
Sign up to set email alerts
|

Measuring smartphone usage and task switching with log tracking and self-reports

Abstract: Smartphones offer multimedia convergence in a single device, ubiquitous access to media, and constant connections with others. The rapid rise of smartphone use calls for more scholarly attention paid to users’ media usage and time expenditure. This study aims to (a) understand smartphone usage patterns by examining time spent using smartphones and task switching between mobile applications (apps), and (b) test the validity of self-reported measures of these behaviors by comparing self-reports with log data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 37 publications
(55 reference statements)
11
104
1
8
Order By: Relevance
“…Many scales have been developed to assess a program’s convenience, satisfaction, usefulness, helpfulness, etc [ 90 ]. Usage patterns document objectively logged data regarding users’ interactions with the system, including records such as login times, length of usage episodes, and clicks on provided messages [ 91 ]. Conversational quality can be measured from users’ subjective evaluation of the conversation’s coherence, naturalness, and fluency.…”
Section: Resultsmentioning
confidence: 99%
“…Many scales have been developed to assess a program’s convenience, satisfaction, usefulness, helpfulness, etc [ 90 ]. Usage patterns document objectively logged data regarding users’ interactions with the system, including records such as login times, length of usage episodes, and clicks on provided messages [ 91 ]. Conversational quality can be measured from users’ subjective evaluation of the conversation’s coherence, naturalness, and fluency.…”
Section: Resultsmentioning
confidence: 99%
“…Tracking applications, installed by users, increased the depth of insights somewhat but interpretation was hindered by operating system restrictions (e.g., Kobayashi & Boase, 2012;Stier et al, 2020). Most recently, scholars have attempted to use the "app category usage" on Android phone users' devices to assess content use (Deng et al, 2019), but even here, scholars were unable to access information such as total screen time or number of notifications or pick-ups. These "new measures" of mobile communication behavior are important, as research has shown that smartphone usage and different forms of psychological wellbeing are interrelated, such as for stress, hyperactivity, and general wellbeing (Kushlev et al, 2016;Orben, 2020;Stiglic & Viner, 2019).…”
Section: Mobile Data Donationsmentioning
confidence: 99%
“…Since we assessed media multitasking using only a small subset of all possible media-multitasking behaviors, an important question for future studies will be to examine whether associations between cognition and media multitasking do exist for other types of media-multitasking behaviors. Furthermore, in conducting these studies it is also important to consider that people tend to underestimate their frequency of switching between media streams (Brasel & Gips, 2011) and that they tend to overestimate the time they spend using media (Deng, Meng, Kononova, & David, 2018). Another recommendation for future studies would therefore be to combine the use of self-report measures with the use of more objective methods such as diaries (Voorveld & Goot, 2013;Wang & Tchernev, 2012), video recordings of behavior (Rigby, Brumby, Gould, & Cox, 2017), and, especially, automatic tracking on a participant's devices (Wang & Tchernev, 2012;Yeykelis, Cummings, & Reeves, 2014).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%